Strategi Berkesan Pengurusan Pusat Sumber Sekolah di Kawasan Bandar: Pendorong Keberhasilan Pendidikan - Razak, Amirul Fahmie Abdul; A. Ghani, Muhammad Faizal; Radzi, Norfariza Mohd (Proceedings Series of Educational Studies, 2024)
In the current digital and information-centric age, the efficient management of school resource centers (SRCs) is vital for improving students' learning experiences and academic achievements. Despite this, many schools face difficulties in optimizing their SRCs due to issues such as limited resources, outdated management techniques, and inconsistent strategic approaches. This study seeks to identify the best management practices employed by SRCs in Kuala Lumpur to overcome these challenges. Using a qualitative approach, interviews were conducted with four key respondents: two library and media teachers and two educational technology officers from the Educational Resource and Technology Sector. Through thematic analysis, the research uncovered several essential practices for effective SRC management, including (i) strategic planning, (ii) systematic material organization, (iii) the provision of guidance and advisory services, and (iv) the implementation of benchmarking processes. The findings reveal that these practices are successfully applied in selected schools, emphasizing their importance in improving SRC management. The study stresses the need for structured and strategic management to enhance student learning and overall school performance. Recommendations for school leaders and policymakers include increasing funding, investing in professional development, strengthening policy frameworks, and integrating technology into SRC management. Additionally, the research calls for continuous evaluation and further studies to address the unique needs of SRCs across diverse educational settings in Malaysia.